Interaction Between Dendritic Cells and Candida krusei β-Glucan Partially Depends on Dectin-1 and It Promotes High IL-10 Production by T Cells - Dinh, Truc Thi Huong; Tummamunkong, Phawida; Padungros, Panuwat; Ponpakdee, Pranpariya; Boonprakong, Lawan; Saisorn, Wilasinee; Leelahavanichkul, Asada; Kueanjinda, Patipark; Ritprajak, Patcharee (Frontiers in Cellular and Infection Microbiology, 2021)
Host-Candida interaction has been broadly studied during Candida albicans infection, with a progressive shift in focus toward non-albicans Candida species. C. krusei is an emerging multidrug resistant pathogen causing rising morbidity and mortality worldwide. Therefore, understanding the interplay between the host immune system and C. krusei is critically important. Candia cell wall β-glucans play significant roles in the induction of host protective immune responses. However, it remains unclear how C. krusei β-glucan impacts dendritic cell (DC) responses. In this study, we investigated DC maturation and function in response to β-glucans isolated from the cell walls of C. albicans, C. tropicalis, and C. krusei. These three distinct Candida β-glucans had differential effects on expression of the DC marker, CD11c, and on DC maturation. Furthermore, bone-marrow derived DCs (BMDCs) showed enhanced cytokine responses characterized by substantial interleukin (IL)-10 production following C. krusei β-glucan stimulation. BMDCs stimulated with C. krusei β-glucan augmented IL-10 production by T cells in tandem with increased IL-10 production by BMDCs. Inhibition of dectin-1 ligation demonstrated that the interactions between dectin-1 on DCs and cell wall β-glucans varied depending on the Candida species. The effects of C. krusei β-glucan were partially dependent on dectin-1, and this dependence, in part, led to distinct DC responses. Our study provides new insights into immune regulation by C. krusei cell wall components. These data may be of use in the development of new clinical approaches for treatment of patients with C. krusei infection.